LuminoCell: a versatile and affordable platform for real-time monitoring of luciferase-based reporters - Weissová, Kamila; Fafílek, Bohumil; Radaszkiewicz, Tomasz; Celiker, Canan; Macháčková, Petra; Čechová, Tamara; Šebestíková, Jana; Hampl, Aleš; Bryja, Vítězslav; Krejčí, Pavel; Bárta, Tomáš (Life science alliance, 2022)
Luciferase reporter assays represent a simple and sensitive experimental system in cell and molecular biology to study multiple biological processes. However, the application of these assays is often limited by the costs of conventional luminometer instruments and the versatility of their use in different experimental conditions. Therefore, we aimed to develop a small, affordable luminometer allowing continuous measurement of luciferase activity, designed for inclusion into various kinds of tissue culture incubators. Here, we introduce LuminoCell-an open-source platform for the construction of an affordable, sensitive, and portable luminometer capable of real-time monitoring in-cell luciferase activity. The LuminoCell costs $40, requires less than 1 h to assemble, and it is capable of performing real-time sensitive detection of both magnitude and duration of the activity of major signalling pathways in cell cultures, including receptor tyrosine kinases (EGF and FGF), WNT/β-catenin, and NF-κB. In addition, we show that the LuminoCell is suitable to be used in cytotoxicity assays as well as for monitoring periodic circadian gene expression.
Keywords: Luciferases; Signal Transduction; signální transdukce; NF-kappa B; luciferasy